Library Management System Design in SMA 6 Madiun - Adiputra, Novega Pratama (Universitas Pendidikan Indonesia, 2024)
Currently, all library lending, returning, and data collection activities at SMA Negeri 6 Madiun are done manually. This is highly inefficient as it wastes paper, generates erroneous data, and results in disorganized and untidy filing. The purpose of this study was to design, build, and implement a website-based library management system at SMA 6. In this study, the system development method used is waterfall. Through the stages of requirements, design, coding and testing, integration and testing, and operations maintenance. The result of this research is the library management system. The conclusion of this study is that a library management system will be able to improve and make work simpler, faster, and more accurate. can facilitate the management and borrowing of books for librarians and library visitors.